Optimalisasi Peran Caregiver dalam Merawat Lansia yang Tinggal di Panti Werdha - Maria Manungkalit; Ni Putu Wulan Purnama Sari (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Entering old age, the elderly will experience a decline in body function both physically and psychologically. This decline can result in a decrease in the physical ability of the elderly in carrying out their daily activities and activities and for this reason the elderly become dependent on others. The purpose of this community service activity is to improve the knowledge and skills of caregivers with health education or counseling methods and physical examination simulations for the elderly who experience health problems. This activity was carried out in August 2025 with a population of 71 caregivers working at the Santo Yosef Werdha Home. The number of participants who attended was 45 people. The instrument used in this activity was a questionnaire that was distributed and filled out before and after the provision of material by the resource person. The results showed that most caregivers before being given the material showed that the level of knowledge was not good, as many as 24 people (53%). After the provision of material, there was an increase in the level of knowledge with the results being mostly in the good category, as many as 38 people (84%). The need for caregiver understanding and skills in caring for and nurturing the elderly through counseling and training can increase the level of caregiver knowledge and have an impact on the quality of care provided to the elderly.